2023
DOI: 10.1186/s40795-023-00682-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits after a physical activity mHealth intervention: a randomized controlled trial

Abstract: Background A healthy diet and a sufficient amount of physical activity are important factors to reduce complications of type 2 diabetes. Diet and physical activity are associated behaviours. Individuals who are physically active have also been shown to have healthier eating habits than sedentary individuals. We aimed to evaluate the indirect effect of a smartphone-based physical activity intervention on dietary habits in patients with type 2 diabetes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…To the best of our knowledge, no intervention studies have focused on enhancing adherence to the Mediterranean Diet in this population. Although exercise can indirectly modify dietary habits [22][23][24][25][26], the present study showed no influence of the exercise intervention on the adherence to the Mediterranean diet. In line with these findings, a previous work conducted in perimenopausal women [38] reported no changes in overall adherence to the Mediterranean Diet following a four-month concurrent exercise intervention.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…To the best of our knowledge, no intervention studies have focused on enhancing adherence to the Mediterranean Diet in this population. Although exercise can indirectly modify dietary habits [22][23][24][25][26], the present study showed no influence of the exercise intervention on the adherence to the Mediterranean diet. In line with these findings, a previous work conducted in perimenopausal women [38] reported no changes in overall adherence to the Mediterranean Diet following a four-month concurrent exercise intervention.…”
Section: Discussioncontrasting
confidence: 71%
“…It is worth mentioning that in the present study adherence to the Mediterranean diet was slightly and consistently enhanced in the exercise group, although this increase did not reach statistical significance. Given that previous research has shown that physical activity interventions can indirectly increase fruit and vegetable consumption [23][24][25][26], it is possible that exercise primarily influences specific food groups within the Mediterranean Diet, rather than the diet as a whole. Therefore, it could be hypothesized that: (i) our exercise intervention could be a stimulus that only produces slight but insufficient modifications in dietary patterns and/or (ii) Mediterranean Diet could be a very specific pattern to be indirectly modified through exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations